INCLUSIVE TEACHING ENVIRONMENT ON TEACHERS’ SELFEFFICACY - Wu, Hao (Top Educational Review Journal (TERJ), 2024)
Education has undergone significant transformations, increasingly prioritizing diversity and inclusion. This study is situated within this context, as it aimed to evaluate the inclusive teaching environment and the self-efficacy of educators, with the ultimate goal of devising an enhancement program, "Empowering Educators for Inclusivity" (EEI), for the institutions under examination. Using a correlation research method, 120 teachers participated in the survey. Results indicated a high level of agreement and consistency in educators’ preparedness and attitudes toward inclusive teaching (mean=3.61), interdisciplinary approaches (mean=3.57), and a critical examination of norms and biases (mean=3.52). Notably, student agency and participation (mean=3.82) ranked highest, demonstrating the strong engagement of students in the learning process. The overall inclusive teaching environment was perceived positively (mean=3.63). Further assessment of self-efficacy revealed strong consensus in support and interaction (mean=3.61), instructional management (mean=3.63), and collaboration (mean=3.65), with adaptability (mean=3.44) identified as an area for improvement. The Pearson r Coefficient of 0.43, with a p-value of 0.000, indicated a moderate, positive, and significant relationship between inclusive teaching environments and educators’ self-efficacy. Based on these findings, the EEI program is recommended to bolster areas of strength and address adaptability needs, with the expectation of enhancing the efficacy and inclusivity of teaching practices at the surveyed institutions.